Design of digital kWh-Meter to top-up the electric pulse by automatically using Relay Module Based on SMS and Arduino Uno - Ramadhani, Syarifah Fitrah; Wahyuningsih, Pujianti; Jalil, Abdul; Suryana, Syarifah (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2022)
This study aims to design a digital kWh-meter prototype to top-up the electricity pulse by automatically using relay modules based on Short Message Service (SMS) and Arduino Uno. The utilization of 12 relay modules to substitute the keypad input function in the digital kWh meter is our basic idea in this study. The method we used to replace the keypad input function with the relay module is based on the integration between the circuit path in the keypad board and the relay module as an electric switch that can activate when the relay gets a trigger from the Arduino Uno. In this study, when the user wants to charge the electric pulse, the user will send the voucher number to the GSM SIM900A module via SMS, then it will be processed to the Arduino Uno. Then Arduino Uno will trigger the relay to be activated so that it can automatically fill the voucher number to the digital kWh-meter. This study result is the success of relay modules can substitute the function of keypad input to fill the voucher pulse number to the digital kWh-meter through SMS with the successful voucher number filling up to 98%. The usefulness of the relay module to change the keypad input function on the digital kWh meter is our original idea for this study.